Improving Corrosion Resistance of Aluminosilicate Refractories towards Molten Al-Mg Alloy Using Non-Wetting Additives: A Short Review - Faranak Barandehfard (Materials, 2020)
The corrosion of refractories in contact with high temperature aluminum-magnesium alloys leads to contamination of the Al-Mg alloy products by solid impurities from degraded refractories. Where both the spinel and corundum phases form in the refractories, cracks are generated and propagated by diffusion of molten Al-Mg, resulting in severe corrosion. In this review paper, the corrosion phenomenon is discussed, and published work is summarized, supplemented by our recent experimental results. Using the Alcan immersion test, materials based on white-fused mullite (WFM) were evaluated for their corrosion resistance and interfacial behavior. WFM was modified using different 2-wt.% of non-wetting additives (NWAs), such as BaSO4, CaF2, Secar®71 cement and wollastonite to improve their performance when in contact with molten Al-Mg alloy at 850 °C for 96 h. The mechanical properties of the samples such as flexural and compressive strength were evaluated, in addition to X-ray diffraction and microscopic analysis (optical and scanning electron microscopy coupled with X-ray elemental mapping). It was observed that cracks formed in samples were promoted with only BaSO4, CaF2, Secar®71 cement or wollastonite. However, cracks did not appear in the sample promoted with both 1-wt.% CaF2 and 1-wt.% BaSO4, because of improved anti-wetting properties in addition to inhibiting spinel (MgAl2O4) formation, which is the main cause of the cracks. This is a significant finding in the prevention of cracks and improvement of the refractory corrosion resistance.